PQS-dependent quorum sensing in pseudomonas aeruginosa is linked to protein export via the twin-arginine translocation (tat) system - Smith, Frances (2022)
Pseudomonas aeruginosa is a leading cause of nosocomial infection due to its inherent resistance to multiple classes of antibiotics and ability to readily form protective antibiotic-tolerant biofilms. P. aeruginosa has a vast number of regulatory systems as well as multiple interlinked hierarchical quorum sensing (QS) systems that allows tight control over its large genome. The PQS-dependent QS system utilises alkyl-quinolones (AQs) as autoinducers, including the Pseudomonas quinolone signal (PQS) and its immediate precursor, 2-heptyl-4-hydroxyquinoline (HHQ). PQS-dependent QS coordinates the production and release of virulence factors, secondary metabolites, rhamnolipids, microvesicles, and extracellular DNA, which are important for biofilm formation. The Twin-arginine transport (Tat) System translocates fully-folded proteins across the inner membrane and inhibition, mutation or deletion of the tat genes resulted in down-regulated PQS biosynthesis. The primary aim of this PhD was to understand why loss of the Tat system causes perturbation of pqs QS. This was studied in two ways, through a) transcriptome analysis and b) mutagenesis of each known Tat substrate to discover whether a single substrate could account for the phenotype.